Comparative Study of Poverty in Indonesia: Multidimensional Poverty And Monetary Poverty - Nuryitmawan, Tegar Rismanuar (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
Research on poverty has long been done by various methods and approaches. Approach to identifying the poor in general by calculating consumption expenditure or income revenue. The calculation is then known as monetary poverty. Indonesia also use and implemented that approach. However, some experts believe that monetary poverty approach does not capture the whole cause of poverty because the indicator calculation not enough. Though poverty is a multidimensional phenomenon that involves not only the economic aspects but involves other aspects. Using secondary data from Indonesian family Life survey, this study proposes to calculate the multidimensional poverty index and estimates the poor based on two approaches, multidimensional poverty and monetary poverty. Calculating the poverty by alkire foster method, whereas to estimate multidimensional poverty and Monetary Poverty using logistic regression. The Results for Alkire-Foster calculation method show that identify of poor by multidimensional poverty greater than the monetary poverty. Generally, the standard of living dimension contributes most to the multidimensional poverty index. Standard living dimension was believed to be the dimension that explains the nature of households that are directly related to the everyday household behavior. Meanwhile, estimation of monetary poverty shows that variable consumption per capita, the head of the household sector employment, hours of work, household size and household asset ownership affect the identification of poverty. Only education variable is not significant effect on the identification of poverty. Base on those finding, education has two possibilities to affect poverty one significant affect multidimensional poverty, while for monetary hasn't affect.